Sensitivity of Capital Market Development to Public Debt in Nigeria - Kalu Onwukwe Emenike; Ugwueze Christian Amu; Ezeji Emmanuel Chigbu (Bina Nusantara University, 2016)
This article investigated the sensitivity of capital market development to public debt in Nigeria using descriptive statistic, regression analysis, and the Engle-Granger co integration techniques for the period ranging from 1981 to 2014. The estimates from the descriptive analysis showed that both the market capitalization and public debt series were not normally distributed at 5% significance level. The ADF unit root test showed that the market capitalization and public debt series were integrated of order one (i.e., I (1)). The results from the regression model provide evidence to show that capital market development is not sensitive to domestic debt at any conventional level, but it is sensitive to external debt at 10% significance level. The estimates of the Engle-Granger co integration tests show that capital market development is not co integrated with public debt. It is recommended that capital market and debt management authorities should formulate policies will enhance linkage between the markets.